Effect of Varying Temperatures on Seed and Seedling Vigour in Bold Seeded Chickpea Genotypes - Naik3, Suneeta Patra1, R.N. Sharma2* and M.L (Journal of Phytology, 2011)
Chickpea (Cicer arietinum L.) known by the common names Bengal gram, gram, homes, garbenzobean is traditionally grown in parts of the world covering Asia, Africa, Europe, North and south America but the bulk of it is produced and consumed in South countries. In India Chickpea is a prime pulse crop of rabi. The present study was performed to see the performance of high yielding bold seeded chickpea genotypes for seed vigour under varying temperature conditions. Performance of five highest yielding bold seeded chickpea under different temperature conditions revealed that 25o C - 30o C temperature was optimum for various seed/seedling vigour tests for chickpea as compared to other temperatures, at which the testing was done.